ASSIMILATION AS AN EFFORT TO OVERCOME THE SPREAD OF CORONA VIRUS ACCORDING TO MINISTER OF LAW AND HUMAN RIGHTS REGULATION NO.24 OF 2021 - Safithri, Hijriyana; Lubis, Ramiah (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The corona virus has become a global epidemic since the last two years, and Indonesia is also included in the country affected by this corona virus outbreak, especially in 2021 the corona virus outbreak is increasing, taking so many victims. Therefore, the Ministry of Law and Human Rights has extended the policy of granting assimilation rights at home for prisoners and children to reduce the density of prisoners in prisons, state detention centers and the Special Child Development Institute (LPKA). The problem is for prisoners, what are the conditions that must be met to obtain assimilation at home and what if the prisoners who have received assimilation at home commit crimes again during the assimilation period at home. The method used in this paper is a qualitative research method. That is by collecting legal materials by reading, quoting, taking notes, and studying reading materials related to research problems, especially the Regulation of the Minister of Law and Human Rights no. 24 of 2021 amendments to Ministerial Regulation Number 32 of 2020 concerning Conditions and Procedures for Granting Assimilation, Conditional Release, Leave Before Release, and Conditional Leave for Convicts and Children in the Context of Prevention and Control of the Spread of Covid-19. The data that has been collected is stated in the form of a description. The data analysis used in this research is descriptive qualitative. Prisoners will obtain assimilation if they have met the requirements contained in Article 11 and Article 45 of the Regulation of the Minister of Law and Human Rights No. 24 of 2021 and if the prisoner commits a crime while carrying out assimilation at home, he will be subject to a heavier sentence than before.